A Comparative Study of Performance Appraisal on Effectiveness and Organizational Commitment - Girdharwal, Nitin (Prabandhan: Indian Journal of Management, 2019)
The study examined the relationship between the organization performance appraisal 'system' and 'process' facets, members' perception of the effectiveness of the appraisal system, and organizational commitment. It was hypothesized that the system and process of performance evaluation would be instrumental in deciding individuals' perception and their degree of 'affective' and 'continuance' organizational commitment. The examination was conducted among respondents (N = 200) from an automobile organization in North India. Regression analysis investigation results demonstrated that the process facets namely, session planning and multiple inputs positively predicted the perceived effectiveness of the performance appraisal system. The results additionally demonstrated that the process aspects - 'multiple input,' 'session feedback,' and 'session planning' were positive predictors of 'affective' organizational commitment, while 'continuation' organizational commitment was positively predicted by both the system facet and the process facet. The findings have significant implications for organizations which endeavor to expand the organization commitment of their individuals by enhancing the effectiveness of the performance appraisal system.